(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
We studied this work investigate the fixed points of modified Kaplan York map k1 and we focus on found contracting and expanding area of this map ,Moreover we study the dynamical system of modified Kaplan York map,is aslo studied the chaotic properties of k1 proved the topological entropy of k1 is positive , k1 is sensitive dependence into initial condition , k1 is transitive finally the Lyapunov exponent is positive .we use mat lab program to show the sensitivity and transitivity of Kaplan York map